The Influence of Company Growth, Funding Decisions, and Dividend Policy on Firm Value - Irnawati, Jeni; Saqina, Regita; Suryanto, Wirawan (MultiTech Publisher, 2024)
There was a decline in the company's growth and value. Corporate growth and corporate value. It's a phenomenon on the financing decision that's undergoing an increase but not at the expense of the company's value. Other phenomena in the food and beverage sector companies listed in the EIB showed fluctuations in the dividend policy while the company's value fell. It's becoming a major issue in this research. The purpose of this research is to find out whether there is an influence of Corporate Growth, Financing Decisions and Dividend Policy on Corporate Value on Food and Beverage Manufacturing Companies Period 2017-2021. The analytical method used is a Time Series and Cross Section analysis by comparing the Company's Growth Rate, Financing Decisions and Dividend Policy to the Company Value with the previous year, and comparing it with the Food and Beverage Sector Manufacturing Company Values Period 2017-2021 that included the criteria in the Objective Sampling. Partially, Corporate Growth has no influence and is not significant to the Corporate Value. The Financing Decision has a significant negative impact on the Company's Value. Dividend policy has no influence or significance on the Company's Value. Simultaneously there is an influence between Corporate Growth, Financing Decisions and Dividend Policy on Corporate Value in Food and Beverage Manufacturing Companies Period 2017-2021.